2005
DOI: 10.1111/j.1525-1497.2005.0083.x
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: If you build it, they will come

Abstract: Background: Latinos have low representation in cancer prevention trials and intervention studies. Culturally appropriate recruitment strategies are needed to address this issue. Objective: To describe and summarize the effectiveness of recruitment strategies used by the Latin American Cancer Research Coalition (LACRC). Design: Descriptive report of recruitment methods. PArticipants: Uninsured Latino immigrants (N=1,170; 77% female, 23% male) from Central and South America recruited to 7 cancer control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 15 publications
0
23
0
2
Order By: Relevance
“…7,14 Thus, developing culturally adapted videos and bilingual education websites may increase Latino’s awareness and knowledge about clinical trials. Indeed, strategies to overcome language and cultural barriers have proven to be successful in recruiting Latinas for cancer prevention and control studies 31 and for clinical trials in particular. 28,32 For instance, the Cancer Therapy and Research Center in Texas developed a strategic focus to improve Latino recruitment into clinical trial, achieving 45% Latino accrual rate in 2012.…”
Section: Discussionmentioning
confidence: 99%
“…7,14 Thus, developing culturally adapted videos and bilingual education websites may increase Latino’s awareness and knowledge about clinical trials. Indeed, strategies to overcome language and cultural barriers have proven to be successful in recruiting Latinas for cancer prevention and control studies 31 and for clinical trials in particular. 28,32 For instance, the Cancer Therapy and Research Center in Texas developed a strategic focus to improve Latino recruitment into clinical trial, achieving 45% Latino accrual rate in 2012.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of diversity in randomized study populations reduces opportunities for discovering effects that may be particularly relevant to underrepresented populations and contributes to inequitable distribution of benefits and risks of trial participation. Studies also show that individuals from medically underserved populations are more likely to be diagnosed with advanced stage diseases that might have been treated more effectively if diagnosed earlier [6]. These racial differences in access to state-of-the-art care contribute to disparities in cancer mortality and survival after cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of a spokesperson for cancer-related health messages has not been well explored but studies that have examined preferences among Hispanics for other health issues have shown varied preferences, depending on the topic [26,27,28,32]. …”
Section: Discussionmentioning
confidence: 99%